Impact of intergenerational community health intervention on adolescents’ views of older adults in Yogyakarta - Rohmawati, Zubaida; Indriani, Indriani; Linawati, Sri Lestari; Fatmawati, Veni; Kyswantoro, Yunita Firdha (Universitas 'Aisyiyah Yogyakarta, 2025)
Low adolescent participation hinders the effectiveness of the Youth Integrated Health Post (Posyandu Remaja). This study evaluates the impact of the NGAJENI Program—an intergenerational intervention based on health education, physical activity, and collaborative arts—on adolescents' perceptions of the elderly and the significance and magnitude of these changes. A cluster quasi-experimental design was implemented in two kelurahan of Mergangsan Sub District, Yogyakarta. Thirty-seven adolescents aged 15–24 years were purposively sampled and allocated by cluster to the intervention group (n = 20) or control group (n = 17). The intervention spanned 3 month and comprised six 90-minute sessions. Perception was measured via a validated 12-item Likert scale (score range 12–60; Cronbach’s α = 0.89) at pre- and post-intervention. Within-group changes were examined using paired t-tests, between-group differences in change scores (Δ) with independent t-tests, and effect sizes calculated by Cohen’s d. Baseline demographics were comparable (all p > 0.05). The intervention group’s mean perception score increased from 40.20 ± 4.15 to 47.10 ± 3.80 (Δ = 6.90; paired t = –8.32; p < 0.001; d = 1.73), while the control group’s score rose from 39.85 ± 4.30 to 42.35 ± 4.05 (Δ = 2.50; paired t = –3.12; p = 0.006; d = 0.60). Independent t-test confirmed significantly greater perceptual change in the intervention cohort (t = 3.97; p < 0.001). The NGAJENI program significantly improves adolescents' perceptions of the elderly and strengthens intergenerational solidarity at the Youth Posyandu.